Potensi Pengembangan Ayam Broiler Di Kecamatan Polombangkeng Selatan Kabupaten Takalar - Nurfadillah, Nurfadillah; Susanti, Handayani Indah; Paly, Muhammad Basir (Anoa: Journal of Animal Husbandry, 2024)
The livestock subsector plays a crucial role in meeting the demand for animal protein in Indonesia, with broiler chicken farming being one of the key areas of development. This study aims to analyze the potential for developing broiler chicken farming in Polombangkeng Selatan District, Takalar Regency. The methods employed include Location Quotient (LQ), Growth, and Share analyses. The results indicate that Polombangkeng Selatan District has an LQ value of 1.18, identifying it as a base sector with the capacity to meet both local and external demand. The Growth analysis shows a positive growth rate of 29.84, while the Share value of 15.92 demonstrates a significant contribution to the regional economy. Based on the positive Growth and Share values, broiler chicken farming in Polombangkeng Selatan is categorized as a leading commodity. These findings suggest that the development of broiler chicken farming in this region holds promising prospects for enhancing both local and regional economic growth.